Representations vs Actions in online behavior: First results from an academic online panel of internet users - Montargil, Filipe (2019)
This communication discusses the first results of the comparative analysis between representations and actions in online behavior using results from an academic online panel of Internet users. This comparative analysis uses two information sources: answers to questions posed to panel members using methods of sociological inquiry and data gathered through a software application that monitors online behavior. The current version of this application is based in a Google Chrome extension that gathers information from the web browser history, for each participant in the panel, allowing to analyse in detail online behavior. Methods of inquiry are used to explore representations and motivations, for these same panel participants. Differences between representations and actions are discussed since the early years of Sociology and systematically researched in the Social Sciences at least since the 1930s (LaPiere, 1934; Bryman, 2012). The very limitations of short and long-term memory to remember everyday events (Foddy, 1996; Roberts, 1985) lead, among other factors, to differences between what people claim to do and what they effectively do. Our panel is still at an early stage, receiving its first Internet users in December 2018. However, it has already about 300 registered members, in a sample that includes female and male users with different working conditions, marital status and age groups. Developing methods for mapping online behavior is a pressing challenge, especially in our dynamic societies, when we spend more and more time connected.